Did dinosaurs invent flowers? Dinosaur-angiosperm coevolution revisited. - Barrett, P; Willis, K (2001)
Angiosperms first appeared in northern Gondwana during the Early Cretaceous, approximately 135 million years ago. Several authors have hypothesised that the origin of angiosperms, and the tempo and pattern of their subsequent radiation, was mediated by changes in the browsing behaviour of large herbivorous dinosaurs (sauropods and ornithischians). Moreover, the taxonomic and ecological radiation of angiosperms has been associated with the evolution of complex jaw mechanisms among ornithischian dinosaurs. Here, we review critically the evidence for dinosaur-angiosperm interactions during the Cretaceous Period, providing explicit spatiotemporal comparisons between evolutionary and palaeoecological events in both the dinosaur and angiosperm fossil records and an assessment of the direct and indirect evidence for dinosaur diets. We conclude that there are no strong spatiotemporal correlations in support of the hypothesis that dinosaurs were causative agents in the origin of angiosperms; however, dinosaur-angiosperm interactions in the Late Cretaceous may have resulted in some coevolutionary interactions, although direct evidence of such interactions is scanty at present. It is likely that other animal groups (insects, arboreal mammals) had a greater impact on angiosperm diversity during the Cretaceous than herbivorous dinosaurs. Elevated levels of atmospheric CO2 might have played a critical role in the initial stages of the angiosperm radiation.